Long-Term Clinical Outcome in Familial and Sporadic Papillary Thyroid Carcinoma. Issue 4 (28th July 2020) - Capezzone, Marco; Fralassi, Noemi; Secchi, Chiara; Cantara, Silvia; Brilli, Lucia; Pilli, Tania; Maino, Fabio; Forleo, Raffaella; Pacini, Furio; Cevenini, Gabriele; Cartocci, Alessandra; Castagna, Maria Grazia
Abstract : Background: The definition and the behaviour of familial papillary thyroid cancer (FPTC) compared to the sporadic form (SPTC) are still debated. Some authors believe that only families with 3 or more affected members represent an actual example of familial diseases. Objectives: The objective of the study was to analyse the clinicopathological features and the outcome of sporadic and familial PTC patients also according to the number of affected members. Methods: Among 731 patients, we identified 101 (13.8%) with familial diseases, 79 with 2 affected members (FPTC-2) and 22 with 3 or more affected members (FPTC-3) followed for a mean period of 10 years. Results: FPTC patients had more frequently bilateral tumour ( p = 0.007). No difference was found between the 2 groups for the other evaluated variables. At the time of the first follow-up (1–2 years after initial therapy), FPTC patients had a higher rate of persistent disease. However, at the last follow-up, the clinical outcome was not different between sporadic and familial patients. When the comparison between SPTC and FPTC was performed, according to the number of affected members, a significant trend between the 3 groups was observed for tumour diameter ( p = 0.002) and bilaterality ( p = 0.003), while we did not observe a significant trend for both response to initial therapy ( p = 0.15) and last clinical outcome ( p = 0.22). Conclusions: Our results suggest that, although the clinicopathological features of FPTC may be more aggressive, the long-term outcome is similar between FPTC and SPTC. A possible explanation is that PTC has a favourable prognosis, even when clinical presentation is more aggressive.